BIOACTIVITY OF ANTIDESMA BUNIUS LEAVES (EUPHORBIACEAE) AND THEIR MAJOR PHENOLIC CONSTITUENTS - Mona E.S. Kassem; Amani N. Hashim; Heba M. Hassanein (European Scientific Journal, ESJ, 2013)
﻿Chromatographic fractionation of the methanol extract of Antidesma bunius leaves afforded six polyphenols, namely, corilagin (1), gallic (2), ferrulic (3) and ellagic (4) acids in addition to the flavone vicinin II (5) and the dimmer amentoflavone (6). Their structures were elucidated by NMR and HRESI analysis. This is the first reported occurrence of the biflavone (amentoflavone) and vicinin in this species. The total phenolic content was estimated at 90 mg/ml of gallic acid equivalent (GAE) per 100 g plant extract using the Folin-Ciocalteu method. Antioxidant biochemical assay of the plant methanol extract was carried out using culture medium of hepatocyte cell lines. An increase in glutathione reductase enzyme and a reduction of the nitric oxide level in the cell culture revealed that A. bunius leaf extract possesses significant antioxidant activity in comparing with quercetine as a reference. The hepatotoxicity and hepatoprotective activities of A.bunius leaf extract and the pure isolated compounds: 1 , 2 and 5 were evaluated by adopting the MTT colorimetric assay. Compounds 1 and 2 revealed a margin of safety on the monolayer hepatocyte with an IC50 > 1000 μg/ml while for 5, IC50 was at 125 μg/ml. The hepatoprotective activities for A.bunius leaf extract, 1 and 2 in comparison to Silymarin (50 μg/ml) were at 6.5, <12.5 and 12.5 μg/ml respectively while 5 did not show hepatoprotective activity at the tested concentrations.